Hubungan Jenis Kelamin dan Pekerjaan dengan Kejadian Hipertensi Pada Pra-Lansia di Puskesmas Ralla - Sulfitra Sultan; Andi Asrina; Arman (Window of Public Health Journal, 2025)
Hypertension is known as a silent killer because many patients do not know they have this disease. Hypertension is defined as a condition when systolic blood pressure exceeds 140 mmHg or diastolic blood pressure exceeds 90 mmHg. This study aims to investigate the relationship between gender and occupation and the incidence of hypertension among the pre-elderly population in the working area of the Ralla Health Center in 2025. The findings suggest that occupation influences hypertension risk, highlighting the need for targeted community health interventions. Data were collected using a questionnaire and analyzed univariately and bivariately with the chi-square test. The results showed no relationship between gender and hypertension (p = 0.591), but a significant relationship with occupation (p = 0.034). For the community in the working area of the Ralla Health Center, it is hoped that they can avoid hypertension by maintaining a balanced diet and adopting a healthy lifestyle.